2023
DOI: 10.1002/btm2.10550
|View full text |Cite
|
Sign up to set email alerts
|

Basic research and clinical exploration of cold atmospheric plasma for skin wounds

Abstract: Skin wounds, such as burns, diabetic foot ulcers, pressure sores, and wounds formed after laser or surgical treatment, comprise a very high proportion of dermatological disorders. Wounds are treated in a variety of ways; however, some wounds are greatly resistant, resulting in delayed healing and an urgent need to introduce new alternatives. Our previous studies have shown that cold atmospheric plasma (CAP) has antibacterial activity and promotes cell proliferation, differentiation, and migration in vitro. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Of particular note was the fact that antibiotic usage in the plasmatreated group was significantly lower (4%) than in the control group (23%), highlighting the potential significance of plasma in combating infection in a clinical setting [97]. This was also supported by various case studies conducted elsewhere in recent publications [98].…”
Section: Direct Application Of Plasma To Tissuementioning
confidence: 56%
“…Of particular note was the fact that antibiotic usage in the plasmatreated group was significantly lower (4%) than in the control group (23%), highlighting the potential significance of plasma in combating infection in a clinical setting [97]. This was also supported by various case studies conducted elsewhere in recent publications [98].…”
Section: Direct Application Of Plasma To Tissuementioning
confidence: 56%
“…Cold atmospheric plasma can interact with biological cells at temperatures below 40ºC and trigger various biological processes. In addition, the fact that cold atmospheric plasma application is non-contact and painless allows it to be easily used on human tissues and cells [23,24]. Studies have shown that cold plasma has a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of the CAP device used in this study has been previously established in both rats and humans. 16 Having demonstrated its ability to inhibit Malassezia yeasts in vitro, we conducted a prospective randomized controlled trial, demonstrating that CAP is a secure and efficient approach for adult MF management. With the prolongation of treatment duration, the therapeutic effect improved.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the CAP device, the so‐called ST‐P101 plasma skin therapy instrument (Hefei CAS Ion Medical and Technical Devices Co., Ltd, Hefei, China), can be found in a paper by Miaomiao Li et al. 16 Briefly, the hand‐held therapeutic electrode head consisted of 1‐mm‐diameter copper needles connected to the reactor, where the high‐voltage electrode was located. The low‐voltage electrode was connected to the skin.…”
Section: Methodsmentioning
confidence: 99%